106k views
3 votes
if
f(x)=(1)/(3) - (1)/(2)x and
g(x) = 2x^(2) + x + 4 find
(f+g)(x)

1 Answer

1 vote

Answer:


\large\boxed{(f+g)(x)=2x^2+(1)/(2)x+4(1)/(3)}

Explanation:


(f+g)(x)=f(x)+g(x)\\\\\text{We have}\\\\f(x)=(1)/(3)-(1)/(2)x,\ g(x)=2x^2+x+4.\\\\\text{Substitute:}\\\\(f+g)(x)=\left((1)/(3)-(1)/(2)x\right)+(2x^2+x+4)\\\\=(1)/(3)-(1)/(2)x+2x^2+x+4\qquad\text{combine like terms}\\\\=2x^2+\left(-(1)/(2)x+x\right)+\left((1)/(3)+4\right)\\\\=2x^2+(1)/(2)x+4(1)/(3)

User Lucas Rodrigues
by
6.4k points